Using Literature to Teach Problem Solving in Mathematics - Bintz, William Paul; Moore, Sara Delano (Ohio Journal of School Mathematics, 2018)
This article provides a snapshot of one interesting, but unexpected, classroom experience that (Author 1) had with a 1st grade student above and what lessons we learned from this student about using literature to teach problem solving in mathematics. It also includes suggested text sets of other literature that can be used to teach students a variety of important mathematical concepts.